1986
DOI: 10.1007/bf01531575
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-beta-hydroxylase (DBH) and homovanillic acid (HVA) in autistic children

Abstract: In the present study, plasma DBH activity and urinary HVA levels were measured in 19 autistic and 15 normal children. DBH activity was significantly elevated in the 8 less retarded autistic patients. In this subgroup, a negative correlation was found between plasma DBH and urinary HVA levels. These results support the hypothesis of a possible involvement of brain catecholamine dysfunction in the production of autistic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…In addition, GATA3 has also been shown to be involved in the development of the central nervous system in mice [95] and the induction of dopamine beta-hydroxylase (DBH) in primary neural crest stem cells [96]. With respect to the latter activity, it is of interest to note that DBH genotype has been associated with autism in some families [97], [98] and that DBH activity has been noted to be elevated in a subgroup of autistic patients [99]. Like the 3 genes discussed above, NFKBIZ, a nuclear regulator of NFKB activity, is also involved in inflammation and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GATA3 has also been shown to be involved in the development of the central nervous system in mice [95] and the induction of dopamine beta-hydroxylase (DBH) in primary neural crest stem cells [96]. With respect to the latter activity, it is of interest to note that DBH genotype has been associated with autism in some families [97], [98] and that DBH activity has been noted to be elevated in a subgroup of autistic patients [99]. Like the 3 genes discussed above, NFKBIZ, a nuclear regulator of NFKB activity, is also involved in inflammation and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In one study (Belmaker, Hattab, & Ebstein, 1978) plasmatic DBH activity was superior in children with various types of psychoses than in children with organic cerebral disease or mental retardation. Recently, Garnier et al (1983Garnier et al ( , 1986 again studied this parameter: They found no difference in DBH activity between controls and autistic children as a group; however a significant increase was observed in autistic subjects without mental retardation compared with patients in which autistic syndrome was associated with signs of mental deficiency.…”
Section: Introductionmentioning
confidence: 94%
“…A significantly higher homovanillylc acid (HVA)/MHPG ratio was found in the CSF of autistic subjects, suggesting an imbalance between the dopaminergic and noradrenergic systems (Gillberg and Svennerholm 1987). Findings concerning serum dopamine-␤ -hydroxylase have been inconsistent and inconclusive (Lake et al 1977;Young et al 1978;Garnier et al 1986). However, to the best of our knowledge, no research on autism has demonstrated significant alterations in platelet [ 3 H]-rauwolscine binding characteristics.…”
Section: Catecholaminesmentioning
confidence: 99%